Pengaruh Penamabahan Puree Daun Katuk (Sauropus Androgynus) dan Bubuk Udang Rebon Terhadap Sifat Organoleptik Crackers Kareb - Annisa Pramesti; Nugrahani Astuti; Niken Purwidiani; Andika Kuncoro (Tarbiatuna: Journal of Islamic Education Studies, 2025)
Crackers are a snack product that is high in carbohydrates and low in protein. This study is an experimental study that aims to determine the effect of the addition of katuk leaf puree and rebon shrimp powder on the organoleptic properties of Kareb Crackers and to determine the nutritional content of the best Kareb Crackers which includes the content of carbohydrates, proteins, fats, fiber, calcium, vitamin A, iron, moisture content, and ash content. The data collection technique used observation techniques to find the best results based on organoleptic trait tests conducted by 20 trained panelists. The data analysis used was Kruskal-Wallis and Mann-Whitney  follow-up tests to find the best results from the organoleptic properties test of Crackers Kareb. The best results were then chemically tested in the laboratory of the Industrial Research and Consultation Center (BPKI). The best Kareb Crackers results are with the addition  of  15% katuk leaf puree and 7.5% rebon shrimp powder with nutritional content per 100 grams of Kareb Crackers which includes, 72.83 g of carbohydrates, 13.85 g of protein, 8.61 g of fat, 3.06 g of fiber, 168.50 mg of calcium, 88.90 mg of vitamin A, 4.80 mg of iron, 1.32 g of water content, 0.31 g of ash content.